1997
DOI: 10.1038/sj.sc.3100413
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the treatment of patients with spinal neoplasms

Abstract: Progress in oncological therapy within the last decade has enhanced the survival time of patients su ering from tumorous osteolyses of the spine. While the necessity of surgical intervention is often settled by acute clinical symptoms, the extent of surgery is certainly codetermined by the patient's expectations and the time of survival to be expected. We therefore developed a speci®c tumor algorithm for operations on the spine with special emphasis on prognosis and the attainable quality of life. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Reasons are the general opinion that extensive rehabilitative efforts may either not be tolerated by the terminally ill patient or be futile because of the limited life span. While there are several studies that report the outcome of primary treatment and recommend an aggressive approach, [3][4][5][6][7][8] there is only limited information about postacute management. 20 consecutive patients confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons are the general opinion that extensive rehabilitative efforts may either not be tolerated by the terminally ill patient or be futile because of the limited life span. While there are several studies that report the outcome of primary treatment and recommend an aggressive approach, [3][4][5][6][7][8] there is only limited information about postacute management. 20 consecutive patients confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, we expect that a combination of both functional and oncological parameters will give the best survival prognosis. Patients with metastatic disease of the spine are subject to extensive surgery, [3][4][5][6][7][8] sophisticated chemotherapy 11,12 or radiation protocols. 9,10 Consequently, SCI -once it is evident that neurological symptoms will not regressshould not be answered with rehabilitative nihilism.…”
Section: Discussionmentioning
confidence: 99%
“…No surgery in group 1 with a very limited life expectancy, a dorsal approach in group 2, and a dorsoventral approach in group 3. 40,41 The revisions performed by Tokuhashi (written communication, June 2004) do not change the results of this study. However, a prospective study will ultimately determine the true value of this score.…”
Section: Discussionmentioning
confidence: 45%
“…Other authors have reported that up to 81% of patients with spinal neoplasm experienced neurological improvement following surgery combining anterior-posterior approaches (33,34). The prognosis for neurological recovery is adversely affected by the degree and duration of canal narrowing, demonstrating that patients may benefit from earlier decompression regardless of the selected surgical procedure (35).…”
Section: Discussionmentioning
confidence: 99%